2023
DOI: 10.1021/acsphotonics.3c01073
|View full text |Cite
|
Sign up to set email alerts
|

Integrated-Resonant Units for Phase Compensation and Efficiency Enhancements in Achromatic Meta-lenses

Jin Yao,
Rong Lin,
Xiaoyu Che
et al.

Abstract: Achromatic meta-lenses have shown great promise in ultracompact and full-color optical devices. Their performances, including size, bandwidth, and numerical aperture, are originally restricted by the phase compensation provided by functional metaatoms. Integrated-resonant units (IRUs), associating various meta-atoms, resonant modes, and functionalities into one supercell, are efficient candidates for large phase compensation in broadband achromatic meta-lenses. In this work, we propose nonlocal plasmonic IRUs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…Recently, studies in metasurfaces have shown that integrated-resonant units (IRUs) present a promising solution to overcome the existing bottleneck in field enhancement. By integrating various resonance modes within one supercell, the IRU not only leverages the intrinsic modes for field enhancement but also promotes interactions among these modes, significantly amplifying the electric field. Furthermore, IRU is capable of engaging nonlocal resonance modes characterized by a collective response from multiple adjacent units . Numerous studies have demonstrated that the nonlocal modes, notable for their high-Q factors, can significantly benefit the effort of field enhancement, which opens up possibilities in diverse fields, such as augmented reality, polarization detection, optical signal sensing, and quantum entanglement …”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies in metasurfaces have shown that integrated-resonant units (IRUs) present a promising solution to overcome the existing bottleneck in field enhancement. By integrating various resonance modes within one supercell, the IRU not only leverages the intrinsic modes for field enhancement but also promotes interactions among these modes, significantly amplifying the electric field. Furthermore, IRU is capable of engaging nonlocal resonance modes characterized by a collective response from multiple adjacent units . Numerous studies have demonstrated that the nonlocal modes, notable for their high-Q factors, can significantly benefit the effort of field enhancement, which opens up possibilities in diverse fields, such as augmented reality, polarization detection, optical signal sensing, and quantum entanglement …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, in recent years, there has been growing interest in the development of nonlocal metasurfaces. Nonlocal metasurfaces have the ability to manipulate phase, wavefronts, and polarization of light in a relatively narrow spectral band by inducing collective oscillations of the constituent units over the supra-wavelength scale, in contrast to local metasurfaces which are operated by spatially localized resonances and have limited Q-factors. Following this, recently developed nonlocal chiral metasurfaces support the chiral resonance with strong CD and a high-Q factor, potentially offering a solution to realize chiral metamaterials with enhanced light–matter interaction at a narrow spectral range. Such nonlocal chiral metasurfaces provide potential applications to chiral emission, nonlinear optics, and optical communications with benefits over broadband ones in the fine-tuning of optical information within a limited bandwidth. ,, One of the common and recent approaches to realizing nonlocal chiral metasurfaces is to induce quasi-bound states in the continuum (q-BIC) by designing the geometry to be broken mirror symmetry. Examples of these include the multi-perturbations in a double-layered metasurface , and out-of-plane symmetry breaking using structures with different heights. More recently, nonlocal chiral metasurfaces in optical frequency were successfully demonstrated by designing and fabricating the in-plane chiral nanostructures at the subwavelength scale. , Despite the progresses, the underlying physics and design rules of nonlocal chiral metasurfaces are not fully revealed compared to the case of local chiral metasurfaces explored for the last decades. In addition, it is still challenging to achieve high-Q stokes parameters detection since the precise and consistent-sized fabrication of the various nanogeometries for targeted S parameters and wavelength with high-Q factor is still elusive and thus has not been demonstrated.…”
mentioning
confidence: 99%